Evolving perspectives of medial temporal memory function: hippocampal processes in visual and auditory forms of episodic and working memory - Hawkins, Chris; Yonelinas, Andrew P. (Frontiers in Cognition, 2024)
A cornerstone of memory science is the finding that the medial temporal lobe plays a critical role in supporting episodic long-term memory. However, the role that this brain region plays in supporting other forms of memory such as working memory is controversial. In this selective review, we describe some of the key studies that have informed our current understanding of the role that the medial temporal lobe plays in working memory. We first describe the early studies that supported the idea that the medial temporal lobe is selectively important for long-term episodic memory function, then discuss the subsequent research that indicated that the hippocampus also plays a critical role in visual perception and visual working memory. We then review more recent work suggesting that the medial temporal lobe, and particularly the hippocampus, is critical in supporting a familiarity-based memory signal in working memory, and we propose that this function may not be limited to the visual domain, but rather may support familiarity for auditory working memory as well.